Mutation-Driven Divergence and Convergence Indicate Adaptive Evolution of the Intracellular Human-Restricted Pathogen, Bartonella bacilliformis. - Sandip Paul; Michael F Minnick; Sujay Chattopadhyay (Public Library of Science (PLoS), 2016)
Among all species of Bartonella, human-restricted Bartonella bacilliformis is the most virulent but harbors one of the most reduced genomes. Carrión's disease, the infection caused by B. bacilliformis, has been afflicting poor rural populations for centuries in the high-altitude valleys of the South American Andes, where the pathogen's distribution is probably restricted by its sand fly vector's range. Importantly, Carrión's disease satisfies the criteria set by the World Health Organization for a disease amenable to elimination. However, to date, there are no genome-level studies to identify potential footprints of B. bacilliformis (patho)adaptation. Our comparative genomic approach demonstrates that the evolution of this intracellular pathogen is shaped predominantly via mutation. Analysis of strains having publicly-available genomes shows high mutational divergence of core genes leading to multiple sub-species. We infer that the sub-speciation event might have happened recently where a possible adaptive divergence was accelerated by intermediate emergence of a mutator phenotype. Also, within a sub-species the pathogen shows inter-clonal adaptive evolution evidenced by non-neutral accumulation of convergent amino acid mutations. A total of 67 non-recombinant core genes (over-representing functional categories like DNA repair, glucose metabolic process, ATP-binding and ligase) were identified as candidates evolving via adaptive mutational convergence. Such convergence, both at the level of genes and their encoded functions, indicates evolution of B. bacilliformis clones along common adaptive routes, while there was little diversity within a single clone.